Single giant mediastinal rhabdomyoma as a sole manifestation of TSC in foetus - Godava, Marek; Filipova, Hana; Dubrava, Lubomir; Vrtel, Radek; Michalkova, Kamila; Janikova, Maria; Bakaj-Zbrozkova, Lenka; Navratil, Jiri (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2017)
BACKGROUND: Presence of multiple cardiac rhabdomyomas is one of the major features of Tuberous sclerosis (TSC), but isolated progressing single giant rhabdomyoma is very rare and not typical of TSC. CASE REPORT: This report presents family without obvious history of TSC with occurrence of giant mediastinal rhabdomyoma affecting the haemodynamics in male foetus, without other TSC symptoms. Girl from the next gravidity had prenatally detected multiple rhabdomyomas and small subcortical tuber of brain detected after birth. DNA analysis found novel c.4861A>T TSC2 variant and large deletion in TSC2 in tumour tissue from male foetus. The novel TSC2 variant was also present in the girl and her healthy father, in silico analysis suggested its functional effect on TSC2. Brain MRI of the father detected mild TSC specific abnormality. CONCLUSION: We suggest the novel TSC2 mutation is a cause of mild TSC in this family and has reduced expression. The clinical and molecular findings in this family also emphasize that TSC diagnosis should be also evaluated in case of single giant foetal cardiac rhabdomyoma.
Keywords: Predictive Value of Tests; Mediastinal Neoplasms; genetická predispozice k nemoci; Autopsy; tuberin; Pregnancy; cardiac rhabdomyoma; Male; mild tuberous sclerosis.; lidé; hamartin; Humans; Genetic Testing; nádorové supresorové proteiny; Tuberous Sclerosis Complex 2 Protein; Abortion, Induced; novorozenec; pitva; prediktivní hodnota testů; Tumor Suppressor Proteins; Tuberous Sclerosis; rhabdomyom; Fetal Diseases; Tuberous Sclerosis Complex 1 Protein; Rare Diseases; TSC2; mužské pohlaví; Genetic Predisposition to Disease; nemoci plodu; Rhabdomyoma; genetické testování; tuberózní skleróza; nádory mediastina; ženské pohlaví; Prenatal Diagnosis; těhotenství; Female; vzácné nemoci; mutační analýza DNA; DNA Mutational Analysis; indukovaný potrat; prenatální diagnóza; Infant, Newborn; reduced expression